Modifikasi Kereb dengan Inovasi Fitur Self-Glow Melalui Penambahan Fosforence dan Glass Bead - Riskina Wilosa Dwiwardani; Reza Alisa Ardyanti; Riza Susanti; Asri Nurdiana (Universitas Diponegoro, 2024)
The increase in population in Indonesia occurs rapidly as the years go by, which is directly proportional to the need for adequate facilities and infrastructure for carrying out activities and mobilizing from one place to another. Fulfillment of multi-story parking facilities is often found in the basement. It can be supported by additional facilities that help vehicle drivers take advantage of limited land. This section is quite dark and can potentially harm drivers because it causes high installation and maintenance costs for electrical installations and lighting. In overcoming this problem, one alternative research effort is to innovate the addition of a self-glow feature by adding phosphorescence powder and glass beads to modifications to conventional carriages' road dividers. Using a layer variation of 30%P1 20%P2; (15%F1;60%T1); (20%F2;80%T2); (25%F3;100%); top coat 100:50 tested for drying time, adhesion test, low-temperature test, softening point test, shelf life test, gradation test, and reflectivity test according to SNI 03-6450-2000. Glass waste was chosen as an additional material because it has the same properties as glass beads in reflecting light. Phosphorescence powder can glow in the dark, while glass beads can reflect light. Then it went through various testing processes (30%P1; 25%; 100%F3), which is an efficient variation and has the quality of the results of the luminescence test and reflectivity test, namely Qd 417, and it can be seen that the water-based phosphorescence coating can light up to 50 minutes at exposure 46.2 lux.